THE PLACE OF YASSAVI’S SCHOLARLY LEGACY IN THE HISTORY OF RESEARCH - Khamzayev, Shavkat Adirasulovich (Oriental Journal of History, Politics and Law, 2025)
This article analyzes the scholarly heritage of Khoja Ahmad Yassavi and the process of its study across different periods. The examination of Yassavi's teachings based on primary sources, as well as scientific research on his Sufi ideas, spiritual and educational views, and literary style, are covered in chronological stages. Additionally, in studying Yassavi's legacy, an overview of scientific works conducted by Eastern and Western scholars, particularly researchers from the Soviet and independence periods, is provided. This analysis demonstrates that Yassavi's legacy holds great significance not only in religious and moral terms, but also in philosophical and literary aspects.